(untitled) - Vasquez, Vivian Maria (London, 2004)
Negotiating critical literacies with young children is specifically useful for early elementary (K-3) teachers as a demonstration of classroom applications of critical literacy that they can try in their own classrooms. It is equally relevant to all concerned with issues of social justice and equity in school settings and the political nature of education, and to educators at all levels who are interested in finding ways to make their curriculum critical. For pre-service teachers, this book offers model for envisioning their future practice and for recognizing the important relationship between theory and practice. Teacher educators and consultants will find this book valuable as an example of how to put a critical edge on teaching. It is intended for use as a text in reading, language, arts, literacy, social justice, critical literacy, and early chilhood education courses.
Keywords: Language arts (early childhood),Language arts (early childhood),Critical pedagogy; Social aspects,Curricula; United States,United States,United States